METHOD CORROBORATION FOR THE DETERMINATION OF HIGH CONCENTRATION OF CHROMIUM IN VARIOUS ALLOYS USING ATOMIC ABSORPTION SPECTROPHOTOMETRY - Khalid, N.; Rahman, S. (The Nucleus, 2020)
Atomic absorption spectrophotometric technique was employed to determine high concentration of chromium as usually found in alloys. Different instrumental parameters, such as wavelength, slit width, burner height and flow rate of fuel were optimized, for the minimum absorption signal with low background. The effect of cations (Al+3, Ca+2, Cd+2, Co+2, Cu+2, Fe+2, K+, Li+, Mg+2, Mn+2, Mo+6, Na+, Ni+2, Sr+2, V+5 and Zn+2) and acids (HCl, HNO3, HClO4 and H2SO4) on the determination of chromium under the optimized conditions was studied. The reliability of the procedure was cross-checked by analyzing the alloy samples with other analytical techniques such as spectrometry, ICP-ES and neutron activation analysis and comparing the results, which are in quite good agreement with each other. The developed procedure was successfully applied for the determination of chromium in various types of alloys.